Inside Cover: Structure–Activity Relationship Studies of Amino Acid Substitutions in Radiolabeled Neurotensin Conjugates (ChemMedChem 1/2016). Issue 1 (January 2016) - Mascarin, Alba; Valverde, Ibai E.; Mindt, Thomas L.
Abstract : The inside cover picture shows that the composition of the amino acid (AA) sequence of a neurotensin‐based radiotracer is crucial to balance its metabolic stability and receptor affinity in order to optimize the tumor targeting capabilities of the conjugate. Evaluation of a set of radiometallated neurotensin derivatives under standardized experimental conditions in vitro enabled, for the first time, a structure–activity relationship study based on the most commonly applied amino acid substitutions reported in the literature. More information can be found in the Full Paper by Thomas L. Mindt et al. onpage 102 in Issue 1, 2016 (DOI:10.1002/cmdc.201500468 ).